EVALUASI KINERJA GURU IPS SMP BERDASARKAN STANDAR KOMPETENSI GURU DI KABUPATEN KEBUMEN - Ria Widarsih; Nahiyah Jaidi Faraz (Harmoni Sosial: Jurnal Pendidikan IPS, 2016)
Penelitian ini bertujuan untuk mengetahui kompetensi pedagogik, kompetensi kepribadian, kompetensi  sosial,  dan kompetensi profesional guru IPS SMP di Kabupaten Kebumen berdasarkan penilaian dari asesor dan penilaian diri sendiri. Jenis penelitian ini termasuk penelitian evaluatif. Model evaluasi yang digunakan adalah model evaluasi benchmarking (bangku ukur). Pendekatan penelitian yang digunakan adalah kuantitatif deskriptif. Populasi penelitian adalah seluruh guru IPS SMP di kabupaten Kebumen. Pemilihan sampel guru IPS dilakukan dengan propotional random sampling sebanyak 134 guru. Teknik pengumpulan data menggunakan angket. Teknik analisis data menggunakan analisis statistik deskriptif dengan persentase. Hasil penelitian membuktikan bahwa: (1) kompetensi pedagogik guru IPS SMP di Kabupaten Kebumen dalam kategori baik dengan persentase sebesar 88,00%; (2) kompetensi kepribadian guru IPS SMP di Kabupaten Kebumen dalam kategori amat baik dengan persentase sebesar 93,09%; (3) kompetensi sosial guru IPS SMP di Kabupaten Kebumen dalam kategori baik dengan persentase sebesar 88,65%; (4) kompetensi profesional guru IPS SMP di Kabupaten Kebumen dalam kategori baik dengan persentase sebesar 79,53%. EVALUATION OF PERFORMANCE OF SOCIAL SCIENCE TEACHERS AT JUNIOR HIGH SCHOOLS BASED ON TEACHER’S STANDARD COMPETENCE IN KEBUMEN REGENCYAbstractThe research objectives were to reveal pedagogical competence, personality competence, social  competence, and professional competence of social science teachers at junior high schools in Kebumen Regency based on the assessor’s assessment and self assessment. This was a evaluation research using bechmarking evaluation model with descriptive kuantitatif. The research population was all social science teachers at junior high schools in Kebumen Regency. The sample, consisting of 134 teachers, was selected using the proportional random sampling technique. The data were collected through questionnaires. They were analyzed using descriptive statistics with percentage. The research finding proved that: (1) pedagogical competence of social science teachers at junior high schools in Kebumen Regency is in the good category with the percentage 88.00%; (2) personality competence of social science teachers at junior high schools in Kebumen Regency is in the very good category with the percentage 93.09%; (3) social competence of social science teachers at junior high schools in Kebumen Regency is in the good category with the percentage each of 88.65%; (4) professional competence of social science teachers at junior high schools in Kebumen Regency is in the good category with the percentage 79.53%.